The Transformation of the English Novel, 1890–1930 - Schwarz, Daniel R. author. aut Link
VIII, 336 p.
Keywords: Focusing on the work of Hardy, Lawrence, Conrad, Joyce, Forster and Woolf, this study is divided into two sections: the first shows how historical and contextual material is essential for developing powerful readings; the second discusses how new theory has transformed the way we read and think.